The Effect of Protease Enzyme and Citric Acid Addition on the Organoleptic Properties of Catfish Head Milk - Welly Deglas; Fransiska Fransiska; Maria Krisna Evania (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
This study evaluated the effects of combining protease enzyme dosages (0.5%, 1%, and 1.5%) with citric acid levels (0.1%, 0.3%, and 0.5%) on the organoleptic quality of catfish head milk, including color, aroma, taste, homogenization/clarity, and panelist acceptance. The product was formulated through enzymatic hydrolysis under controlled pH conditions and subsequently assessed using a sensory scoring scale. The results showed that the treatments significantly affected color (F = 4.13; p < 0.05), homogenization (F = 2.39; p < 0.05), and overall hedonic preference (F = 3.03; p < 0.05), but had no significant effects on aroma (F = 1.62; p > 0.05) or taste (F = 1.39; p > 0.05). Specifically, the best color was obtained at 0.5% protease and 0.5% citric acid (A1B3), while the highest homogenization occurred at 0.5% protease and 0.1% citric acid (A1B1). In terms of overall liking, the highest score was recorded at 1.5% protease and 0.5% citric acid (A3B3), followed by 0.5% protease and 0.3% citric acid (A1B2). However, when considering the balance among all attributes (color, aroma, taste, and homogenization), the combination of low protease with low to moderate citric acid levels (0.5% protease; 0.1–0.3% citric acid) provided the most stable performance, producing a relatively bright color, more acceptable flavor and aroma, and better physical stability. Overall, the enzymatic hydrolysis approach with moderate pH adjustment proved effective at enhancing sensory acceptance and offers a promising method for transforming low-value fish by-products into consumer-preferred functional food products